(3OQGSI ebGQfIs - (3hdjO MjOQ(B, (3LGHQs ((3HjQhJ(B:s (3efThQGJ GdMdHj GdMbhbjI(B,s, 2009)
(3GdJahjV JMO bGfhfj GbJUGOj eDSSGJj , ehVhY JbfjI GdJahjV , ehbY JbfjI GdJahjV ef GdWQb GdGNQi aj JfajO GdeQab GdYGe , GdfXGe GdbGfhfj dJbfjI GdJahjV , YbO GOGQI h GSJKeGQ GdeQab GdYGe (B: (3YbO GOGQj (B.(3Gdehba GdaQfSj ef GdJMcje , Gdehba GddHfGfj ef GdJMcje (B.s
(3eQGLY U(B.657 (3; GdeUWdMGJ U(B.655s
Keywords: (3GdEOGQI GdYGeIs; (3GdGSJKeGQs; (3GdJahjVs; (3GdeQGab GdYGeIs